The Role of Victim’s Assistant to Prevent Secondary Victimization : Case Women Victim of Marital Rape - Jenny Rahayu Afsebel Situmorang; Vinita Susanti (HUMANISMA : Journal of Gender Studies, 2021)
Women (wives) is the most hidden victim of marital rape. Regarding this issue, we argue that women victims need victim assistance to prevent secondary victimization. This article is based on a literature review with a qualitative approach. Turning to marital rape cases in Indonesia, women's victims get harmful impacts in physiological and physical. Women victims of marital rape in Tanjung Priok, Bali, Pasuruan, and "L" are some of them. We conclude that the government and other stakeholders need to provide victim assistance for women victims of marital rape in mental and physical health, legal services (advocacy), economic empowerment, campaign, and particular public services spaces. The first thing to do is mental and physical health, but the next part, like legal services, is essential to prevent secondary victimization. Therefore, campaign to build awareness from society is essential to prevent stigmatization for women victims of marital rape. Finally, to implementing the role of victim assistant to prevent secondary victimization in marital rape cases needs unity for people by people and institution by institution. It is needed the same standpoint about marital rape.  Perempuan (secara khusus istri) merupakan korban tersembunyi dari pemerkosaan dalam pernikahan (marital rape). Menanggapi hal tersebut, menjadi penting untuk mempertimbangkan peran pendampingan korban atau victimassistance untuk menghindari viktimisasi sekunder (secondary victimization). Adapun artikel ini berdasarkan penelusuran literatur (literature review) dengan pendekatan kualitatif. Mengacu pada kasus marital rape yang dialami perempuan (istri) di Indonesia, maka hal tersebut berdampak buruk secara fisik maupun psikologis. Perempuan di Tanjung Priok, Bali, Pasuruan dan “L” merupakan contoh korban marital rape. Kesimpulan tulisan ini yaitu mendorong pemerintah dan pihak terkait agar segera menyediakan layanan pendampingan perempuan korban marital rape secara fisik, psikologis, bantuan hukum, pemberdayaan ekonomi, kampanye dan layanan di ruang publik. Hal yang pertama dilakukan adalah pendampingan layanan fisik dan mental. Kemudian, membangun kesadaran publik agar perempuan korban marital rape tidak distigmatisasi. Akhirnya, untuk menerapkan peran victimassistant sebagai pencegahan secondary victimization bagi perempuan korban marital rape membutuhkan kesatuan dari berbagai pihak dan lembaga. Persepektif yang sama terkait marital rape jelas dibutuhkan.